Penerapan Balutan Kompresi Pada Ulkus Kaki: Literature Review - Shanty Chloranyta; Kadek Yuke Widyantari; Tiara Rica Dayani (Malahayati Nursing Journal, 2022)
ABSTRACT Common chronic wounds are foot ulcers. Foot ulcers that do not heal most often result from venous insufficiency. The treatment that can be applied to treat chronic wounds caused by damage to the veins is by reducing distension of the leg veins and accelerating venous blood flow. The purpose of this review article is to determine the appropriate application of compression dressings on foot ulcers based on previous studies. In this review article, the author uses three databases, namely Ebscohost, Google scholar, and Pubmed. From the search results, articles are selected based on their suitability to the specified topic and keywords. From the search results, articles are selected based on their suitability to the specified topic and keywords. The inclusion criteria were articles discussing venous le ulcers, compression bandaging, randomized control trials and systematic reviews or meta-analyses for the search year 2016-2021, and full-text journals. The exclusion criteria were that the article was not in full text, not in accordance with the research objectives. The findings from this article review are the analysis of the appropriate dressing used on venous ulcers due to venous insufficiency is a four-layer compression bandage. 4 layer compression dressing can increase wound healing time and reduce wound size. The healing time of leg ulcers due to venous insufficiency with four-layer compression increased wound healing time with an average healing time of 73.6 ± 14.64 days in the four-layer group and decreased wound size from 5 to 10 cm 2 . Compression dressings are effectively applied to venous leg ulcers. Keywords: 4 layer compression, venous leg ulcer, wound healing time ABSTRAK Luka kronis umumnya yang terjadi yakni ulkus kaki. Ulkus kaki yang tidak sembuh sebagian besar dapat diakibatkan oleh insufisiensi vena. Upaya yang dapat diterapkan untuk mengobati luka kronis akibat kerusakan vena adalah dengan mengurangi distensi vena tungkai dan memperlancar aliran darah vena. Tujuan dari review artikel ini adalah untuk mengetahui penerapan balutan kompresi yang tepat pada ulkus kaki berdasarkan penelitian-penelitian yang sudah dilakukan sebelumnya. Dalam review artikel ini, penulis menggunakan tiga database yaitu Ebscohost, Google cendekia, dan Pubmed. Dari hasil penelusuran, dipilih  artikel berdasarkan   kesesuaian dengan topik dan kata kunci yang ditetapkan. Kriteria inklusi yakni artikel yang mendiskusikan tentang vena leg ulcer, compression bandaging, random control trial dan systematic review atau meta analysis tahun pencarian 2016-2021, dan jurnal fulltext. Kriteria eksklusi yakni artikel tidak fullteks, tidak sesuai dengan tujuan penelitian.   Temuan dari review artikel ini adalah analisis balutan yang tepat digunakan pada ulkus vena akibat insufisiensi vena yakni balutan kompresi 4 layer. Balutan kompresi 4 layer dapat meningkatkan waktu penyembuhan luka dan menurunkan ukuran luka. Waktu penyembuhan luka ulkus kaki akibat insfisiensi vena dengan kompresi 4 layer meningkatkan waktu penyembuhan luka dengan rentang waktu rerata penyembuhan adalah 73,6 ± 14,64 hari pada kelompok 4 lapis dan menurunkan ukuran luka dari 5 hingga 10 cm2. Balutan kompresi 4 lapis lebih efektif diterapkan pada ulkus vena kaki. Kata kunci: kompresi 4 layer, venous leg ulcer, waktu penyembuhan luka